The Role of Accounting Professional Ethics in Preventing Fraud at the Rabani Sharia Cooperative: Peran Etika Profesi Akuntan dalam Mencegah Terjadinya Fraud di Koperasi Syariah Rabani - Fitri Pebriani; Widyasari (Journal of Creative Power and Ambition (JCPA), 2026)
Fraud is a serious threat that can cause significant financial losses in various forms such as corruption, manipulation of financial reports and misuse of assets for organizations, including cooperatives. This practice can damage the integrity and trust in the company’s financial information which can result in misleading stakholders in making decisions. The purpose of this study is to analyze the role of the accounting profession’s code of ethics in preventing audit fraud in the financial statements of the 2025 rabani sharia cooperative. This research method uses a qualitative approach based on case studies with secondary data obtained from cooperative annual reports, articles. To evaluate the application of ethical code principles, such as objectivity and professionalism, relevant to fraud prevention. The results of this study show that consistent application of the acoountant’s code of ethics can prevent and minimize the risk of fraud and increase public trust in financial reports. This study provides empirical evidence regarding the importance of understanding a strong internal control system and effective management oversight in fraud prevention efforts to prevent similar cases from occurring in the future.